Consumption of folk medicine in men-seeking treatment for infertility - Abdulaziz Baazeem; Thamer Mishal M. Alqurashi; Yasser Homaidi H. Alharbi; Raad Abdullah D. Aldahhas; Mutaz Hassan A. Fatani (Urology Annals)
Background: Male infertility is a major health problem that can have a tremendous negative impact on the affected individuals and couples. The use of folk medicine is common practice in the Middle Eastern region, especially before seeking conventional medical treatment. Unfortunately, some of these remedies might be potentially harmful. This study aims to assess the use of folk medicine before formal medical evaluation by a male infertility specialist among men in couples with subfertility in Saudi Arabia. Materials and Methods: A retrospective study of prospectively documented data was conducted among male patients who presented for evaluation of their infertility at one center in Jeddah, Saudi Arabia, from May 1, 2020, to April 30, 2021, to assess the prevalence of the use of traditional medicine among these patients. Results: The total number of patients who visited the center for infertility assessment during the specified period was of 427. Most patients had primary infertility (64.4%). Table 1 summarizes the demographic data of the patient population. About 55.3% of the patients were 40 years old or less. Patients who consumed some form of alternative medicine are 38.9%. A clinical varicocele was detected in 57.8% of these men. Patients who use alternative medicine had significantly lower semen concentration and estradiol levels (P = 0.02 similarly). Conclusion: About 38.9% of patients who attended our clinic were using some alternative medicine. Furthermore, patients who use alternative medicine had significantly less sperm motility and progressive motility.